Indoor Air Quality in a Cardiac Care Unit (CCU) under Different Ventilations - Salman, Abdulhadi M.; Monem, Ali A.; Khazal, Emad A. (Basrah Journal for Engineering Sciences, 2021)
A proper ventilation offered warranty for a perfect indoor environment. Indoor air environment includes indoor thermal environment and indoor air quality (IAQ). In this paper a numerical investigation of the indoor environment in different ventilations was accomplished. The Cardiac Care Unit (CCU) in Al-Rifai hospital in Thi-Qar governorate was chosen to be investigated, and its thermal achievement and indoor air quality in the hot summer weather were simulated. For the numerical study, the fluent technique used to set up the physical and numerical model of CCU. An attention has been paid carefully to considerate the distributions of the temperature and the velocity fields, followed by an argument of two different ventilation patterns; up-in and up-out ventilation (UV) and displacement ventilation (DV). After making the comparison, it was noticed that the displacement ventilation (DV) is clearly super than that of the up-in and up-out ventilation (UV) due to improvement in the indoor air quality.